Pengaruh Latar Belakang Pendidikan Orang Tua terhadap Motivasi Belajar Siswa Kelas VI SDI Tompokersan Lumajang pada Mata Pelajaran al Quran dan al Hadist - Moh. Muafi Bin Thohir; Ifan Ali Alfatani; Ubaidillah Ubaidillah (PGMI ISMAA, 2025)
Education is truly something that has a role as a foundation in human life. Therefore, the implementation of education must be carried out as well as possible and oriented towards the future. The purpose of education is to form individuals who are faithful, pious, have good morals, are healthy, knowledgeable, capable, creative, independent, and become responsible and democratic citizens. Education also aims to develop the potential of students to achieve safety and happiness, both as individuals and members of society. This study uses a quantitative approach with a correlational research type. The population in this study were all sixth grade students of SDI Tompokersan Lumajang. Data collected using the following methods. 1) Questionnaire, which is to collect data on the educational background of students' parents on students' learning motivation, 2) documentation is used to dig up data on the population. Data analysis used in this study is regression test and correlation test. The results of the study show that: (1) there is a positive and significant influence between the background of elementary level parental education on student learning motivation, indicated by a significance value of 0.007 ˂ 0.05. (2) There is a positive and significant influence between the background of middle level parental education on student learning motivation, indicated by a significance value of 0.008 ˂ 0.05. (3) There is a positive and significant influence between the background of high level parental education on student learning motivation, indicated by a significance value of 0.044 ˂ 0.05. (4) There is a positive and significant influence between the overall level of parental education on student learning motivation, indicated by a significance value of 0.045 ˂ 0.05. It can be concluded that M that there is a significant influence between variables X together on Y, so it can be concluded that H1 is accepted and Ho is rejected.